(untitled) (Journal of Parents and Teachers, 2014)
This article echoes one of the top novels of Spanish literature: The ingenious hidalgo Don Quixote de la Mancha. Thus, it exposes how this personage is present in the cinema, in didactic units, in the human rights and even in the hip-hop.